Nail bed injuries and deformities of nail - R Ravindra Bharathi; Babu Bajantri (Indian Journal of Plastic Surgery)
Nail bed injuries are common and management of these requires good knowledge of the nail bed anatomy. Proper management of these injuries will ensure good healing and prevent late deformities. When loss occurs it is challenging to reconstruct which can be done by grafts or microsurgical reconstruction to restore aesthetic appearance of fingers.